2009
DOI: 10.3174/ajnr.a1657
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hippocampal Malrotation in a Population without Seizures: Fig 1.

Abstract: BACKGROUND AND PURPOSE:Hippocampal malrotation (HIMAL) is a failure of hippocampal inversion that occurs during normal fetal development and has been seen on MR imaging examinations of people with epilepsy, but it has not been studied in patients without epilepsy. We intended to evaluate the prevalence of HIMAL in MR imaging examinations of patients without seizures to better understand the significance of HIMAL in the population with seizure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 2 publications
2
77
0
7
Order By: Relevance
“…Follow-up imaging of these children should help determine whether IHI predisposes them to temporal lobe epilepsy and mesial temporal sclerosis. Therefore, imaging findings of IHI may raise suspicion of an underlying potential for the presence of a seizure disorder (7). All patients with hippocampal atrophy were excluded from our study since their hippocampi were collapsed and they may not have preserved the original form.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up imaging of these children should help determine whether IHI predisposes them to temporal lobe epilepsy and mesial temporal sclerosis. Therefore, imaging findings of IHI may raise suspicion of an underlying potential for the presence of a seizure disorder (7). All patients with hippocampal atrophy were excluded from our study since their hippocampi were collapsed and they may not have preserved the original form.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,12,31 The exact definition of HIMAL has been debated, and the inclusion of multiple, potentially related findings has not been accepted by all researchers. 1,12 The association between HIMAL and febrile status has also recently been questioned. 9 Even the term "hippocampal malrotation" has been debated as an appropriate term with some authors suggesting that "incomplete hippocampal inversion" is a more embryologically appropriate description.…”
Section: Developmental Factorsmentioning
confidence: 99%
“…1,12 Some studies have also demonstrated an increased prevalence of this morphology in children with febrile status epilepticus, suggesting that there may be an etiological link, 31 although this has recently been questioned. 9 This morphology has been variously described depending on the defining criteria chosen in each study (e.g., "hippocampal malrotation," or HIMAL, "incomplete hippocampal inversion," or "hippocampal morphologic modification").…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bernasconi and colleagues, observed hippocampal malrotation in 49% of 76 patients with malformations of cortical development, and 43% of 30 patients with temporal lobe epilepsy and 10% of 50 healthy control patients 3 . In 497 patients without epilepsy who underwent MRI, no patients had all diagnostic features of hippocampal malrotation but six patients had two or more features 6 . In this issue of the journal, Andrade and colleagues reported hippocampal malrotation using 3 Tesla MRI in 9 of 14 adults with 22q11.2 deletion syndrome, a population with a 7 fold increased risk of developing epilepsy compared to the general population 7 .…”
mentioning
confidence: 99%